Design and development of transcutaneous electrical stimulation equipment for neuromuscular rehabilitation in individuals with facial palsy - Quintero, Jorge Eduardo; Manotas, Gioanny Francisco; Galeano, Yuber Alejandro; Tellez, Diego Mauricio (TECCIENCIA, 2014)
Peripheral facial palsy is a relatively common pathology that is usually unilateral. Multiple causes generate it, producing aesthetic and functional deformity, as well as emotional, social, and professional alterations. We developed electronic equipment for transcutaneous electric stimulation, which will be applied in neuromuscular rehabilitation treatments of individuals who have suffered peripheral facial palsy. Electrotherapeutic energy is generated through current sources, whose waveforms consist of rectangular biphasic pulses, which can be adjusted in their duration or width, frequency, and intensity. For patient electrical safety, the equipment is powered with batteries. The waveforms generated and the therapeutic parameters are controlled through a microcontroller. What differentiates this equipment from the few found in the market, for this rather specific application, is that it was designed with four independent channels for passive therapy, which permits stimulating more than one neuromuscular package at the same time, and also has one channel for active therapy, which is dynamically applied by the therapist by moving the active electrode over the surface of the face.